Effect of Zn(2+) on the Adsorption of Male-Specific Filamentous Deoxyribonucleic Acid and Isometric Ribonucleic Acid Bacteriophages - Ou, Jonathan T. (1972)
By means of both electron microscopy and plaque assay techniques, 10(−3)m Zn(2+) has been shown to reduce the adsorption rate of male-specific filamentous deoxyribonucleic acid bacteriophages to the tips of F pili. In contrast, 10(−3)m Zn(2+) did not affect the adsorption of male-specific ribonucleic acid phages to the sides of F pili.